Dominica : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
Over the past five years, Dominica has experienced rising fiscal deficits and increasing debt levels, associated mainly with slow adjustment to declining growth rates, and an increase in commercial borrowing to finance public investments. In an effort to stabilize the economy, the government entered into a Standby Arrangement with the IMF in late August 2002. The implementation of the stabilization program under this agreement was intended to achieve a reduction in the government's deficit and to eliminate all domestic arrears by the end of FY2003, however performance to date has been questionable. With the IMF Standby Arrangement in place, the rules governing financial management are key to ensure that government spending remains within the fiscal constraints currently facing the economy. In tandem with this program, Dominica has requested technical and financial assistance from the World Bank in the form of an Economic Recovery Support Operation (ERSO). This operation, currently under preparation, would support the government's effort to regain economic sustainability and promote growth while mitigating the impacts of adjustment and protecting past social gains.